Dengue infection in the nervous system: lessons learned for Zika and Chikungunya - Puccioni-Sohler, Marzia; Roveroni, Natalia; Rosadas, Carolina; Ferry, Fernando; Peralta, Jose Mauro; Tanuri, Amilcar (Arquivos de Neuro-Psiquiatria, 2017)
Dengue, Zika and Chikungunya are emerging arboviruses and important causes of acute febrile disease in tropical areas. Although dengue does not represent a new condition, a geographic expansion over time has occurred with the appearance of severe neurological complications. Neglect has allowed the propagation of the vector (Aedes spp), which is also responsible for the transmission of other infections such as Zika and Chikungunya throughout the world. The increased number of infected individuals has contributed to the rise of neurological manifestations including encephalitis, myelitis, meningitis, Guillain-Barré syndrome and congenital malformations such as microcephaly. In this narrative review, we characterize the impact of the geographic expansion of the vector on the appearance of neurological complications, and highlight the lack of highly accurate laboratory tests for nervous system infections. This represents a challenge for public health in the world, considering the high number of travelers and people living in endemic areas.
Keywords: Zika virus infection; Dengue; Chikungunya fever; Neurology